2009
DOI: 10.1007/s00535-009-0155-2
|View full text |Cite
|
Sign up to set email alerts
|

Strong CD8+ T-cell responses against tumor-associated antigens prolong the recurrence-free interval after tumor treatment in patients with hepatocellular carcinoma

Abstract: Our results suggest that strong TAA-specific CD8(+) T-cell responses suppress the recurrence of HCC. Immunotherapy to induce TAA-specific cytotoxic T lymphocytes by means such as the use of peptide vaccines should be considered for clinical application in patients with HCC after local therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(81 citation statements)
references
References 31 publications
3
77
0
1
Order By: Relevance
“…Although the magnitude of the TAA-specific CD8 + T cell response (40) and the precursor frequency of TAA-specific T cells (41) correlates with prolonged tumor-free survival in some studies, even very large numbers of TAA-specific T cells do not alter tumor progression in others (42). Therefore, variant peptide vaccines also need to expand an effective portion of the TAAspecific T-cell repertoire, which is dependent on the structure of the variant peptide and the cross-reactivity of the responding T cells (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Although the magnitude of the TAA-specific CD8 + T cell response (40) and the precursor frequency of TAA-specific T cells (41) correlates with prolonged tumor-free survival in some studies, even very large numbers of TAA-specific T cells do not alter tumor progression in others (42). Therefore, variant peptide vaccines also need to expand an effective portion of the TAAspecific T-cell repertoire, which is dependent on the structure of the variant peptide and the cross-reactivity of the responding T cells (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Further study suggesting a role for CTL responses in HCC are shown by Hiroishi at al., where they determined that a vigorous CD8+ T-cell response against tumor antigens is associated with a prolonged recurrence-free period after treatment with trans-arterial chemoembolization or radiofrequency ablation [45]. They tested CTL response by interferon-3 ELISPOT to a pool of peptide antigens derived from GPC3, NY-ESO-1 and MAGE-1.…”
Section: Immunotherapeutic Gpc3 Vaccinementioning
confidence: 99%
“…Parallel analysis of T cell responses specific for a panel of different tumor-associated antigens (glypican-3, NY-ESO-1, and MAGE-1) has demonstrated that the magnitude of tumor antigen-specific T cell responses represent the only significant prognostic factor for a prolonged tumor-free interval after interventional therapy for patients with HCC. This indicates that strong tumor-specific CD8+ T cell responses can control the recurrence of HCC [28] . …”
Section: Presence Of Antigen-specific T Cell Responsesmentioning
confidence: 99%